2022
DOI: 10.1093/ndt/gfac107.004
|View full text |Cite
|
Sign up to set email alerts
|

FC052: Atrasentan for the Treatment of IGA Nephropathy: Interim Results from the Affinity Study

Abstract: BACKGROUND AND AIMS IgA nephropathy (IgAN) is the most common primary glomerulonephritis in the developed world. Up to 40% of patients with IgAN are at risk of progressing to end-stage kidney disease (ESKD), with proteinuria being a strong predictor of disease progression. Treatments that reduce proteinuria in IgAN are accompanied by eGFR preservation and improved kidney outcomes.[1] Endothelin A (ETA) receptor activation is a key driver of proteinuria, inflammation and fibrosis in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Interim analysis of AFFINITY demonstrated a 58.5% mean proteinuria reduction in patients with IgAN treated with atrasentan at 24 weeks, and a favorable safety profile. 57 ALIGN also met its primary endpoint on interim analysis, with treatment with atrasentan resulting in a statistically significant reduction in proteinuria compared to placebo at 36 weeks. 58…”
Section: Current Guidelinesmentioning
confidence: 99%
“…Interim analysis of AFFINITY demonstrated a 58.5% mean proteinuria reduction in patients with IgAN treated with atrasentan at 24 weeks, and a favorable safety profile. 57 ALIGN also met its primary endpoint on interim analysis, with treatment with atrasentan resulting in a statistically significant reduction in proteinuria compared to placebo at 36 weeks. 58…”
Section: Current Guidelinesmentioning
confidence: 99%
“…A protocol prespecified interim analysis of the IgAN cohort of the AFFINITY trial reported the baseline characteristic of this cohort at the European Renal Association meeting, 2022. Following a 12 and 24‐week of treatment with atrasentan, there was a mean 24‐h urine protein reduction from baseline of 50% and 59%, respectively with no significant weight gain or acute change in eGFR 79 . Finally, aprocitentan, an orally active, daily dosing, non‐selective ERA has an ongoing phase 3 randomized clinical trial (PRECISION) evaluating its efficacy and safety in patients with treatment resistant hypertension receiving multiple antihypertensives (NCT03541174).…”
Section: Endothelin Receptor Antagonists For the Treatment Of Non‐dia...mentioning
confidence: 99%
“…Following a 12 and 24‐week of treatment with atrasentan, there was a mean 24‐h urine protein reduction from baseline of 50% and 59%, respectively with no significant weight gain or acute change in eGFR. 79 Finally, aprocitentan, an orally active, daily dosing, non‐selective ERA has an ongoing phase 3 randomized clinical trial (PRECISION) evaluating its efficacy and safety in patients with treatment resistant hypertension receiving multiple antihypertensives (NCT03541174). A press release recently reported the PRECISION study achieved its primary endpoint measure of systolic blood pressure reduction at 4 weeks in both the aprocitentan 12.5 mg ( p < .005) and 25 mg ( p < .005) groups compared with placebo, and was well‐tolerated.…”
Section: Endothelin Receptor Antagonists For the Treatment Of Non‐dia...mentioning
confidence: 99%